Study the effect of addition alcoholic extract of Tribulus terrestris on bovine oocyte maturation in vitro (IVM): Imad M. AL-Maeeni1, Khulood W.AL- Samaree2 and Liqaa Y. Abdul Rhman1 - AL-Maeeni, Imad M. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study included 98 bovine ovary collected from AL-Shulla slaughter house immediately after the animal was slaughtered. Ovaries were preserved in physiological saline at 37 Co and transport to the laboratory within 3-4 hrs. Diameters of the follicles were measured and divided into large (6-10 mm) and small (1-5 mm) follicles. Cumulus-oocyte complexes (COCs) were aspirated from large and small follicles using a 18 G needle connected to a 10 ml syringe COCs surrounded by compact and thick cumulus cell were cultured in an integrated culture media RPMI-1640 , than were divided in to two groups , the first group (control media) using integrated culture media only , the second group alcoholic extract of Tribulus terrestris (Tt) plant was added to the culture media RPMI-1640 once a concentration of 50μg/ml , and the other a concentration of 25μ/ml . The results of the current study demonstrated superiority of alcoholic extract of 50μg/ml in the percentage of oocytes maturation which optended or drawn from large and small follicles compared with a concentration of 25μg/ml of the alcoholic extract it was observable the effect of adding alcoholic extract of T. t. plant in two concentrations of 25μg/ml and or 50μg/ml on the percentage of mature oocytes compared to control media (culture media RPMI-1640) .The present results indicated that the oocytes retrieved from larger follicles is better than small follicles in maturing oocytes maturation. In conclusion, alcoholic concentration of 50μg/ml preference extracted first and then the concentration of 25μg/ml T. t. plant extract that was added to culture media RPMI-1640 , superiority in percentage of the mature oocytes compared to control culture media RPMI-1640 , also the large follicle were better than small follicles in terms of equality suitable for mature oocytes.